Influence of substrate composition on size and chemical state of ion beam synthesised Co nanoparticles – Towards fabrication of electrodes for energy devices. (March 2023) - Gupta, P.; Jovic, V.; Hübner, R.; Anquillare, E.; Suschke, K.; Smith, K.E.; Markwitz, A.; Waterhouse, G.I.N.; Kennedy, J.
Abstract: A one-step approach to synthesize ultrafine transition metal particles (size < 5 nm) in carbon substrates is highly desirable for fabricating electrodes for energy devices. Herein, cobalt ion implantation into amorphous carbon films (a:C) and hydrogenated amorphous carbon films (a:CH) was explored, with the aim of synthesizing ultrafine metallic cobalt nanoparticles at room temperature. Co ions of 30 keV energy were implanted into the carbon films to achieve a Co areal density of 1.0 ± 0.1 × 10 17 atoms cm −2 . Rutherford backscattering measurements revealed that hydrogenated amorphous carbon films gave a broader Co depth distribution compared to the amorphous carbon films. Further, cross-sectional TEM analysis revealed that hydrogenated carbon films suppressed metallic Co nanoparticle aggregation, leading to the creation of ultrafine Co nanoparticles (size < 5 nm). Co L -edge X-ray absorption spectroscopy measurements confirmed the formation of predominantly metallic Co nanoparticles by ion implantation. Results conclusively demonstrate that the presence of hydrogen (∼ 28 at%) in the carbon matrix facilitates the synthesis of ultrafine metallic Co nanoparticles during Co ion implantation. Graphical Abstract: ga1 Highlights: Transition metal implantation into carbon results in metallic nanoparticles. High implantation dose is required to maximise nanoparticle density. Ultra-fine nanoparticles are realised when using hydrogenated carbon as substrates. Adding hydrogen broadens implantation profile from room temperature diffusion. Without hydrogen, nanoparticles agglomerate into metallic networks.